Młodzieżowa rada gminy jako przykład uczestnictwa młodzieży w życiu społeczno-politycznym - Brol, Michał (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Youth district councils as an instance of youth participation in socio-political life The aim of this article is to present the issue of youth councils of municipalities in the broader context, namely in this case, the social and political participation of young people in the local communities. Author systematise the knowledge about the forms of youth activity at the local level, proposes a comprehensive definition of youth district councils, and also shows the functions that perform this type of structure. The article is a political science analysis of the phenomenon rather not discussed in field of self-government literature. Key words: youth district councils, social participation, political participation